Urban household credit card debt behaviour in East Malaysia: a conceptual framework - Nur Shahirah Azman; Aminah Shari; Haneffa Muchlis Gazali; Mohamad Azmi Abdullah; Najwa Mohd Khalil (2015)
Society in the modern world nowadays see debt as something normal. Hence, household seems difficult to escape themselves from debt. Credit Counselling and Debt Management Agency (AKPK) recorded from 50,361 cases that enrolled in debt management program, 10.6 percent households could not pay their credit card debt while the remaining had repayment problem with housing loans, car loans and credit cards outstanding (Nie, 2010). The development of credit card facility as a medium of payment to buy goods and services also encourage household to spend beyond their means. Given the increase of cost of living like subsidy restructuring like petrol, increase in tariff electricity and also the implementation of Goods and Services Tax (GST) among the factors which induce the use of credit card to accommodate their cost of living. At the same time, credit card issuer such as financial and nonfinancial also contributed to the increase of household debt by giving easy terms and condition with low interest rate. Therefore the objective of this research is discuss on related literature reviews and follows by the development of conceptual framework that determine urban household credit card debt by integrating psychological factors, bank’s policy factors and socio-demographic factors. Next, this paper also will discuss methodology instrument that will be used for this study.